Determinants of workers absenteeism in the private sectors companies. A case study in Shah Alam, Selangor / Muslihah Atikah Soenarto - Soenarto, Muslihah Atikah (2019)
The purpose of the study is to determine the determinants of workers absenteeism in private sector companies which located in Shah Alam, Selangor. There are four (4) objectives of the study. The first research objective is to determine the relationship between stress, leadership, health conditions, work life balance and workers absenteeism. Next, the research objective is to determine the level of workers absenteeism. The third research objective is to determine the most significant predictors of workers absenteeism. Finally, the research objective is to determine significant effect of gender between stress, leadership, health conditions, work life balance and workers absenteeism. In 2017, Malaysian employees lose 67 days a year to absenteeism due to poor health and fitness. The average yearly cost of health-related absenteeism per organisation is estimated at RM2.7 million. This is just one of the findings of the 2017 Malaysia's Healthiest Work Place by AIA Vitality on 47 small, medium and large-sized companies in cities across Malaysia. Based on past research, it shows that the rate of workers absenteeism is increasing year by year. In this study, questionnaire was used in order to collect the data. The data was analysed by using SPSS version of 26.0. Based on the SPSS data, the researcher found that stress is the most significant factor that influencing the workers absenteeism. It is also found that the level of worker absenteeism in Shah Alam, Selangor is high. Apart from that, all of the factors have significant relationship with the workers absenteeism. Finally, the researcher found that gender had no effect towards stress, leadership, health conditions, work life balance, and workers absenteeism.